Kongebilleder: Ikonografi, ikonoklasme og suverænitet i den tidlige engelske republik - Hasberg Zirak-Schmidt, David (K&K - Kultur og Klasse, 2022)
This article analyses a conflict between royalist iconography and republican iconoclasm in the visual strategies of the frontispieces to Eikon Basilike and Eikon Alethine, two works that react to the execution of Charles I in 1649. The article argues that the clash between these two visual strategies is emblematic of a clash between a republican and an absolutist notion of sovereignty current in Caroline England. The absolutist notion of sovereignty may be meaningfully approached through Walter Benjamin’s theory of the ambiguous nature of early modern sovereignty. For Benjamin, the early modern sovereign is simultaneously a tyrant and a martyr. This double nature of the figure of the sovereign is the result of early modern political theology. The republican notion of sovereignty, which develops in the 1640s, is characterized by its emphasis on popular sovereignty. According to this view, only parliament could legitimately represent the interests of the commonwealth. However, the republican conceptualization of sovereignty ultimately fails because it fails to visually represent the abstract notion of popular sovereignty.